Validity of Buffer Solution e-Module based on Problem Based Learning - Effendi, Novicha; Iryani, Iryani (Entalpi Pendidikan Kimia, 2023)
The Validity of buffer solution e-modules based on problem-based learning has been conducted. This study aimed to determine the category of Validity of buffer solution e-Modules based on Problem-Based Learning (PBL) has been developed. The type of research conducted is educational design research (EDR) with a plomp development model. The Plomp development model consists of 3 stages: preliminary research, prototyping stage, and assessment phase. However, this research is limited to the prototype III. Validation of e-modules using a questionnaire instrument consisting of content, constructs, graphics and language aspects. Seven validators validate the module. The results of the validity data analysis show that the module generated meets the valid criteria in terms of content, constructs, graphics and language aspects.